Citrate, low pH and amino acid limitation induce citrate utilization in Lactococcus lactis biovar diacetylactis. Issue 2 (7th December 2017) - van Mastrigt, Oscar; Mager, Emma E.; Jamin, Casper; Abee, Tjakko; Smid, Eddy J.
Summary: In Lactococcus lactis subsp. lactis biovar diacetylactis, citrate transport is facilitated by the plasmid‐encoded citrate permease (CitP). In this work, we analysed regulation of citrate utilization by pH, nutrient limitation and the presence of citrate at four different levels: (i) plasmid copy number, (ii) citP transcription, (iii) citP mRNA processing and (iv) citrate utilization capacity. Citrate was supplied as cosubstrate together with lactose. The citP gene is known to be induced in cells grown at low pH. However, we demonstrated that transcription of citP was even higher in the presence of citrate (3.8‐fold compared with 2.0‐fold). The effect of citrate has been overlooked by other researchers because they determined the effect of citrate using M17 medium, which already contains 0.80 ± 0.07 mM citrate. The plasmid copy number increased in cells grown under amino acid limitation (1.6‐fold) and/or at low pH (1.4‐fold). No significant differences in citP mRNA processing were found. Citrate utilization rates increased from approximately 1 to 65 μmol min −1  gDW −1 from lowest to highest citP expression. Acetoin formation increased during growth in an acidic environment due to induction of the acetoin pathway. Quantification of the relative contributions allowed us to construct a model for regulation of citrate utilization in L. lactis biovar diacetylactis. This knowledge will help to select conditions to improve flavour formation from citrate. Abstract : Regulation of citrate utilization by pH, nutrient limitation and the presence of citrate has been studied in Lactococcus lactis biovar diacetylactis. More specifically, we investigated the impact of these parameters on citP transcription, on the copy number of the citP containing plasmid, on processing of citP mRNA and on citrate utilization capactity.